Penentuan Lokasi Optimal Cabang Bisnis Kursus EEC Pematang Siantar Menggunakan Metode Analytical Hierarchy Process - Purba, Johannes Duta Christy; Silalahi, Melati; Siahaan, Veby; Gabriela, Reggina; Tupa Ronauli Silalahi, Fitriani (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2024)
Business opportunities are increasing, determining strategic locations as a way to optimize profits. One of them, of course, is that EEC Siantar needs to expand, choose an optimal new location based on the criteria: rental price, capacity, distance to school, competitors, accessibility, distance to the pemilik's house, and population density. This study is to determine the optimal branch location of EEC with AHP. This study uses AHP to select optimal EEC Pematang Siantar course branch locations using pair comparison and priority criteria. The optimal location is selected based on the highest priority value and logistical consistency (CR < 0.1). Ease of accessibility has the highest weight (0.379), followed by buildings (0.379), closest distance to school (0.272), competitors (0.179), distance to homepemiliks (0.085), and population density (0.052). Ease of accessibility is an important factor in determining the location of a new branch. Alternative 3 has the highest final weight (0.413), ahead of Alternative 1 (0.303) and Alternative 2 (0.284). This shows that Alternative 3 has the most optimal combination of subcriteria for new branch locations. This study helps the EEC industrial course select the best new branch locations with the AHP method, increasing the market and profits.